Analysis Satisfaction of Geriatri Outpatients Assessed From the Quality of Service, Perception, and Response Time in Karangploso Public Health Center, Malang District - Izzah El Maila; Nurwijayanti Nurwijayanti; Sentot Imam Suprapto (Journal for Quality in Public Health, 2021)
The role of health workers in administering health services is very important, especially as health service implementers, so it is natural that the ability and performance of health workers is one of the determinants of success in health services. The purpose of this research is to analyze Outpatient satisfaction in terms of service quality, perception and response time at Karangploso Public Health Center, Malang District. The design of this study was an observational quantitative study with a cross sectional approach with a sample of 105 respondents which is taken by Accidental Sampling technique. The finding result shows that p-value of 0.000 <0.05, H1 is accepted so it can be concluded that simultaneously there is an effectservice quality, perception and response time to outpatient satisfaction geriatricsat the Karangpploso Public Health Center, Malang District with the amount of influence of 84%. In patient satisfaction, it is influenced by various things, namely the suitability between the patient's expectations and the reality that the patient meets in the field, the second form of service during the service process provided by health workers and the responsiveness of health workers to patients.